A produção da infância e da criança: um cirandar pelos pareceres pedagógicos na educação infantil - Uecker, Taciana (2019)
This master’s thesis was developed in the Postgraduate Program in Public Policies and Educational Management, in the research line Pedagogical Management and Educational Contexts. It comes from the Research Group in Special Education and Inclusion from the Federal University of Santa Maria – UFSM, Brazil. This research aims to discuss how teachers, (re)produce discursive and non-discursive practices that have been producing a way of saying and being of childhood and of child in the context of an Early Childhood Education Institution, through the analysis of the teachers’ speech and writing actsin their pedagogical reports. The research problem is: how the pedagogical reports produced by early childhood teachers, trigger some knowledge to produce a certain type of childhood and child? Methodologically, by the analogy with a ciranda (a Brazilian child dance characterizedbytheformationof a circleandwhosemembers dance movingaround), withthe sieve used in Brazilian garimpos and with the movement made by them, I sought to understand, from the pedagogical reports produced by Early Childhood teachers, first, about the knowledges that legitimize the way of saying about childhood and child; second, to identify how the study and the analysis of such reports can create other ways of thinking andproducing another perspective of saying about childhood and child indeed. The research, inspired by the Foucault studies, operates on the rules and normality notion. From this, I highlight three analytical units, created by me, in which I discuss this childhood and child conception within an Early Childhood Education Institution. For this, I propose, through reflections, other possibilities of thinking and idealizing childhood. As a product from this master’s thesis, I propose anextension project to Early Childhood teachers training in which it would be considered the (re)signification of childhood, taking as reference the possibility of analyzing the contexts of its conception, and the fact that, from social and cultural relations, sometimes, naturalized, teachers simply reproduce the past childhood in our time.